ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI ACEH TAHUN 2011-2015 - Utami, Mulyana; Ningsih, Endang Surasetyo (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The study aims to evaluate the level of effectivity of the revenue of local taxes and retributions and their contribution for over local own-source revenue over the period of 2011-2015. Using quantitative descriptive method, the research applies documentation technique in collecting data through budget realization statements of districts/cities in Aceh Province. The results show that (1) the revenue of local taxes over period 2011-2015 categorized as very effective. (2) the revenue of local retributions over the year 2011-2015 categorized as less effective. (3) the revenue of local taxes contibute to local own-source revenue over the fiscal year 2011-2015 are projected in medium level. (4) the revenue of local retributions contibute to local own-source revenue over the year 2011-2015 are projected in medium level. (5) revenue of local taxes and retributions and their contribution toward the local own-source revenue are not significantly increase.